1982
DOI: 10.1002/bms.1200090808
|View full text |Cite
|
Sign up to set email alerts
|

Determination of formaldehyde in biological tissues by gas chromatography/mass spectrometry

Abstract: A quantitative method is described for the determination of formaldehyde in biological tissues by stable isotope dilution using gas chromatography/mass spectrometry. (13C2H2)Formaldehyde is used as the isotopic diluent. After tissue homogenization, derivatization is carried out in situ with pentafluorophenylhydrazine, followed by extraction and analysis using selected ion monitoring. The sensitivity of the technique is higher than that of conventional methods of formaldehyde analysis, enabling endogenous forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…A method of headspace gas chromatography revealed that the concentrations of FA in human urine were between 0.019 and 0.048 mM [34]. Moreover, the endogenous FA concentrations in brain samples of control mice detected in the current study were approximately 0.27 mM, which is consistent with the previous reports using HPLC-Fluo [20], HPLC-UV [19], and GC–MS [17]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A method of headspace gas chromatography revealed that the concentrations of FA in human urine were between 0.019 and 0.048 mM [34]. Moreover, the endogenous FA concentrations in brain samples of control mice detected in the current study were approximately 0.27 mM, which is consistent with the previous reports using HPLC-Fluo [20], HPLC-UV [19], and GC–MS [17]. …”
Section: Discussionsupporting
confidence: 90%
“…The earliest determination method for measuring FA in brain tissues (~0.16–0.24 mM) was carried out using gas chromatography/mass spectrometry (GC–MS) [17]. Another sensitive method, developed for the detection of FA in the liver, utilized high-performance liquid chromatography with an ultra violet detector (HPLC-UV) [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the concentration of endogenous formaldehyde was detected at ~0.1 mM in the blood of rats, monkeys, and humans (22,44–46). In addition, endogenous formaldehyde was found to be 2–4 times higher in the liver and nasal mucosa than in the blood of a rat (47). Endogenous formaldehyde is also formed in cellular nuclei, secondary to demethylation of histone III (42).…”
Section: Discussionmentioning
confidence: 99%
“…This indirect effect of HCHO could be the cause of the higher prevalence of asthma and chronic bronchitis found among children exposed to this toxicant [2], Potential mechanisms by which HCHO may facilitate sensitization to high-molecular-weight allergens include in creased permeability of respiratory epithelium and destruc tion of suppressive immunological barriers. From the stud ies on mice and rats it is already known that inhaled HCHO is deposited in the nasal cavity 10-100 times more efficient ly than in other tissues [15]. Changes in the integrity of the upper respiratory tract epithelium are observed in the stud ies employing different animal species.…”
mentioning
confidence: 96%